India-A Focus Point for the International Art Market (New Avenue of Modern Trade) - Rani, Archana (Journal of Commerce and Trade, 2010)
Modern technological changes have given rise to social and economic growth. This emphatical change has girdled the mindsets, the thinking process, and the feelings which have steadily altered both our sensibilities and our means of perception. With these advances alternative routes are emerging towards work of art that has more enduring appeal. New trends in art-media art, video and sound installation, video projections have been experimented by the artists in the field of visual arts. The development in Indian art market where Indian art has taken a new platform. It no longer needs patronage like older times. Earlier the world art market was dominated by European or western art. Now through globalization and awareness there is a radical shift in the mindset of art collector and investor who is now focusing on eastern art and Indian art.